Mont Terri Rock Laboratory, 20 Years Two Decades of Research and Experimentation on Claystones for Geological Disposal of Radioactive Waste (Swiss Journal of Geosciences Supplement,, 2018)
The international Mont Terri rock laboratory in Switzerland plays a central role in the safety and construction of deep geological nuclear repositories in clay formations. The laboratory has developed and refined a range of new measurement and evaluation methods: it has e.g. advanced the determination of rock parameters using innovative borehole geophysics, improved the methodology for characterizing pore-water and microbial activity in claystones, and greatly improved our understanding of diffusion and retention processes of radionuclides in and through claystones. The methods and insights described in this compendium can also be applied to low-permeability rocks at various sites around the globe, and in other fields of application.